Amniotic Membrane Transplantation (AMT) Success Rate in Non-Healing Corneal Ulcers - Mehak Fatima, Maha Sehar, Muhammad Sarfraz (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Cornea is the outermost fibrous layer of the eye that is nourished by tears and aqueous humor and lacks blood vessels. One of the main causes of ocular morbidity is corneal ulcers. Non healing corneal ulcers are those that, inspite of appropriate topical medication, do not heal within a period of 2 weeks. These ulcers can result in descemetocele development and perforation. Nowadays, amniotic membrane transplantation (AMT) is regarded as the preferred course of treatment for these ulcers. Objective: To determine the amniotic membrane transplantation (AMT) success rate in patients of corneal ulcers that do not heal. Study Design: Descriptive case series Settings: Ophthalmology Department, Ward No. 15, Nishtar Hospital Multan. Duration of Study: 6 months, from February 2023 to July 2023. Patients & Methodology: This study comprised 86 patients, both male and female, aged 20-70 years, who has been diagnosed with non healing corneal ulcers. Age, gender, height, weight, body mass index(BMI), diabetes and duration of corneal ulcer among the baseline demographics recorded. AMT was positioned stromal side down and the procedure success rate was recorded one month following the transplant. Results: Mean age was 47.23 ± 13.31 years. Mean BMI was 24.96 ± 4.21 kg/m2. Mean duration of corneal ulcer was 7.26±3.05 months. Mean corneal ulcer size before treatment was 5.16 ± 1.34 mm and after treatment was 0.68±1.22 mm. Mean pain score before treatment was 5.93 ± 1.04 and after treatment was 1.24 ± 1.50. There were 60 (69.77%) males and 26 (30.23%) female patients. Diabetes was diagnosed in 17 (19.77%) patients. Success of AMT was observed in 76 (88.37%) and AMT was unsuccessful in just 10 (11.63%) patients. Conclusion: By encouraging epithelial repair, reducing discomfort and inflammation without causing any complications, amniotic membrane transplantation can effectively treat severe corneal ulcers that are not responding to medical treatment. Keywords: Amniotic membrane transplantation, corneal ulcer.